Effect of salicylhydroxamic acid on mycelial growth and baseline sensitivity to azoxystrobin in Phytophthora infestans causing potato late blight in Thailand - Nalumpang, S.; Poti, T.; Akimitsu, K. (International Journal of Agricultural Technology, 2021)
Late blight of potato caused by Phytophthora infestans is proved to be an aggressive pathogen. Azoxystrobin, a broad spectrum quinone outside inhibitor (QoI), has been used in potato cultivation, but not directly recommended to use to control late blight disease. In this study, a suitable method to determine the sensitivity of P. infestans against azoxystrobin and azoxystrobin sensitivity to P. infestans population was recorded in Chiang Rai and Chiang Mai, Thailand. The toxicity of SHAM was proved a nessary of SHAM addition to artificial media for an efficient determination of azoxystrobin sensitivity. Increased of SHAM concentration led increased mycelial inhibition. SHAM at concentration of 5 to 10 µg/ml showed less effect to mycelia growth of six representative isolates with means of 5.33 to 12.06% inhibition. Both concentrations of SHAM were applied with azoxystrobin for pre-in vitro sensitivity determination. Effective concentration for 50% inhibition (EC50) of azoxystrobin without SHAM was 0.0873 µg/ml, and the sensitivity were significantly increased in azoxystrobin amended with SHAM at 5 and 10 µg/ml for 55.34 and 70.90%, respectively. SHAM at 5 µg/ml was used for in vitro sensitivity assay to azoxystrobin. The thirty-six isolates of P. infestans were determined their azoxystrobin sensitivities based on EC50 evaluation. The mean EC50 value of isolate was 0.0531 µg/ml and ranged from 0.0005 to 0.4415 µg/ml indicating that azoxystrobin was very effective to control the mycelial growth of P. infestans isolated from Chiang Rai and Chiang Mai, Thailand